Molecular dynamics simulation of thermal welding morphology of Ag/Au/Cu nanoparticles distributed on Si substrates. (17th August 2020) - Ren, Xiaoying; Li, Xiao; Huang, Chenchen; Yin, Hailong; Wei, Fengqi
Abstract: The behavior of Ag/Au/Cu nanoparticles dispersed on Si substrates during heat treatment was studied by molecular dynamics in this paper. Whether for the thermal welding of homogeneous metal nanoparticles or heterogeneous metal nanoparticles, it was found that the fundamental reason for the contact between the surface of metal nanoparticles is the electron exchange, which reduces the energy of the system and leads to welding contact, then the atoms migrate toward the interior of nanoparticles through nucleation and growth process, resulting in the decrease of the porosity and the shrinkage of the sample. At the same time, the simulation results show that when the applied temperature rises to a certain extent, the adjacent nanoparticles may condense into isolated structures under their own surface tension and stress, as well as the adhesion of the substrate, which will make the conductive structure discontinuous. However, by adjusting the size and proportion of Ag/Au/Cu metal nanoparticles, besides saving the cost of printing circuits, the conductive structure can be more continuous and the conductivity can be enhanced.